2019
DOI: 10.1002/nag.2941
|View full text |Cite
|
Sign up to set email alerts
|

The difficult challenge of modelling the non‐linear elastic behaviour of soils within a theoretically sound framework

Abstract: Summary Hypo‐elastic relations are often adopted to simulate the recoverable non‐linear behaviour of soils within elasto‐plastic constitutive models. In reality, they are unable to reproduce the elastic, ie, recoverable, response of materials; hence, they introduce severe inconsistencies in models based on the decomposition of the total strain tensor into its recoverable and permanent parts. Hyper‐elasticity should then be used. However, existing models developed within this framework do not satisfy a number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The free energy function proposed by Houlsby et al (2005) may be used as its convexity has been confirmed by Lagioia and Panteghini (2019), who investigates the convexity of several existing hyperelastic free energy functions for soils. Lagioia and Panteghini (2019)…”
Section: Free Energy Functionmentioning
confidence: 87%
“…The free energy function proposed by Houlsby et al (2005) may be used as its convexity has been confirmed by Lagioia and Panteghini (2019), who investigates the convexity of several existing hyperelastic free energy functions for soils. Lagioia and Panteghini (2019)…”
Section: Free Energy Functionmentioning
confidence: 87%
“…von Mises and Drucker‐Prager) and strain energy potentials (e.g. Houlsby, 28 Lagioia and Panteghini 29 ), often dropping one or two of the three invariants, resulting in incomplete formulations. For example the third invariant is dropped in the Drucker–Prager criterion, thus loosing the dependency on the relative magnitude of the intermediate principal stress.…”
Section: Yield Function For the Cosserat Continuummentioning
confidence: 99%
“…Let σ and μ indicate the stress and couple-stress tensors conjugated in the meaning of Hill [6] to the strain γ and wryness χ tensors introduced in Eqs. ( 8) and (9). The rate of the internal work of deformation over the volume Ω is Ẇint =…”
Section: Staticsmentioning
confidence: 99%
“…von Mises and Drucker-Prager) and strain energy potentials (e.g. Houlsby [7], Lagioia and Panteghini [9]), often dropping one or two of the three invariants, resulting in incomplete formulations. For example the third invariant is dropped in the Drucker-Prager criterion, thus loosing the dependency on the relative magnitude of the intermediate principal stress σ II with respect to σ I and σ III , where σ I ≥ σ II ≥ σ III .…”
Section: Equivalent Von Mises Stressmentioning
confidence: 99%